Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/cas.14407
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to trastuzumab/pertuzumab or to T‐DM1 in vivo can be overcome by HER2 kinase inhibition with TAS0728

Abstract: HER2‐targeting antibodies (trastuzumab, pertuzumab) and a HER2‐directed antibody‐drug conjugate (trastuzumab emtansine: T‐DM1) are used for the treatment of HER2‐overexpressing breast cancer. However, these treatments eventually become ineffective due to acquired resistance and there is an urgent need for alternative therapies. TAS0728 is a small‐molecule, irreversible selective HER2 kinase inhibitor. In the present study, we established new in vivo models of cancer resistance by continuous exposure to a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…8D). TDM1 treatment alone in EGFstimulated cells did not alter p-ERK, p-AKT, p-HER2, or p-HER3, in agreement with previous observations [42,43]. Lovastatin did not induce significant alterations in signaling, but when combined with TDM1 it reduces phosphorylation of both ERK and AKT in EGF-stimulated cells.…”
Section: Statins Enhance Tdm1 Efficacysupporting
confidence: 91%
“…8D). TDM1 treatment alone in EGFstimulated cells did not alter p-ERK, p-AKT, p-HER2, or p-HER3, in agreement with previous observations [42,43]. Lovastatin did not induce significant alterations in signaling, but when combined with TDM1 it reduces phosphorylation of both ERK and AKT in EGF-stimulated cells.…”
Section: Statins Enhance Tdm1 Efficacysupporting
confidence: 91%
“…31 In lesions that developed resistance to ado-trastuzumab emtansine, HER2-HER3 phosphorylation was retained, which is why changing therapy to TAS0728 resulted in significant tumor regression due to HER2-HER3 pathway inhibition. 31 Alternative agent that can be used to counter the resistance developed against adotrastuzumab emtansine is ARX788, a novel anti-HER2 antibody-drug conjugate. 32 Wang et al found that the cells that were resistant to ado-trastuzumab emtansine had overexpressed Yes, which in turn activated EGFR, PI3K, and MAPK pathways.…”
Section: Clinical Use Controversiesmentioning
confidence: 99%
“…2 Another proposed therapy to overcome resistance to ado-trastuzumab emtansine therapy is TAS0728, an irreversible selective HER2 kinase inhibitor. 31 In lesions that developed resistance to ado-trastuzumab emtansine, HER2-HER3 phosphorylation was retained, which is why changing therapy to TAS0728 resulted in significant tumor regression due to HER2-HER3 pathway inhibition. 31 Alternative agent that can be used to counter the resistance developed against ado-trastuzumab emtansine is ARX788, a novel anti-HER2 antibody-drug conjugate.…”
Section: Clinical Use Controversiesmentioning
confidence: 99%
“…TAS0728 has demonstrated antiproliferative activity against HER2 overexpressed cancer cells in a dose-dependent manner in vitro and in vivo [ 2 ]. In xenograft models of tumors with acquired resistance to trastuzumab/pertuzumab or to T-DM1, HER2 kinase inhibition with TAS0728 produced significant anti-tumor effects [ 7 ]. A first-in-human phase I dose-escalation study was initiated to investigate safety and dose-limiting toxicity (DLT) and to determine the maximum tolerated dose (MTD) and/or recommended phase II dose (RP2D) of TAS0728 in patients with advanced solid tumors with HER2 or HER3 aberrations.…”
Section: Introductionmentioning
confidence: 99%